Effects of physical activity on college students’ interpersonal competence: chain-mediated effects of self-control and prosocial interpersonal emotional management - Ni, Weidi; Chen, Lili (Frontiers in Psychology, 2025)
IntroductionCollege students often struggle with developing strong interpersonal competence, which is essential for psychological well-being and social adaptation. Although the benefits of physical activity are widely recognized, the specific psychological mechanisms through which it enhances interpersonal competence remain underexplored. This study, therefore, addresses this gap by examining the mediating roles of self-control and prosocial interpersonal emotional management in the relationship between physical activity and interpersonal competence.MethodsA questionnaire survey was conducted on 847 conveniently sampled college students (Man = 382, Woman = 465, Mage = 19.22 years) in Shanghai. Pearson’s correlation analysis and chain mediation effect test was used to examine the correlation between physical activity, self-control, prosocial interpersonal emotion management, and interpersonal competence.ResultsThe results showed that interpersonal competence was positively correlated with physical activity, self-control, and prosocial interpersonal emotional management; physical activity was positively correlated with both self-control and prosocial interpersonal emotional management; and self-control was positively and significantly correlated with prosocial interpersonal emotion management. Higher physical activity predicts better interpersonal competence. Moreover, physical activity can indirectly affect interpersonal competence through the single mediating effects of self-control and prosocial interpersonal emotional management and the chain mediating effect of both.DiscussionThe study shows that physical activity may contribute to students’ psychological well-being and supports the development of their emotional regulation and interpersonal skills. Thus, physical activity must be integrated into university education and mental health interventions to promote college students’ individual and social development.